Toward Intent-Aware, Adaptive Cloud Systems - Faisal, Abdullah Bin (Tufts University Tisch Library, 2025)
Thesis (Ph.D.)--Tufts University, 2025.; Submitted to the Dept. of Computer Science.; Advisor: Fahad Dogar.; Committee: Raja Sambasivan, Hari Sundar, Mark Hempstead, and Varun Gupta.; Keywords: Artificial intelligence, and Systems science